Review paperSearch for a new biomarkers of contrast-induced nephropathy – NGAL (neutrophil gelatinase-associated lipocalin) could be a predictor of contrast-induced nephropathy in high-risk patients diabetes and chronic kidney disease? - Małyszko, Jolanta; Bachórzewska-Gajewska, Hanna (Przegląd Kardiodiabetologiczny/Cardio-Diabetological Review, 2009)
Contrast-induced nephropathy is defined as occurrence de novo of acute renal failure or an abrupt worsening of kidney function after contrast agent administration (after exclusion of other causes). Contrast induced nephropathy is the leading cause of hospital-acquired acute renal failure accounting up to 10% of acute renal failure in the hospital setting, leading to the rise in hospital costs and prolonged hospitalization. Risk factors for contrast-induced nephropathy could be non-modifiable: chronic kidney disease, diabetes, age, diminished ejection fraction, chronic heart failure, hypertension and modifiable: osmolality and ionization of contrast agent, volume of contrast agent, number of injections, dehydration, myocardial infarction within the last 24 h, hypotension etc. In the recent studies value of NGAL (neutrophil gelatinase-associated lipocalin) was highlighted as potential new and early biomarker of acute kidney injury. In the review the role of NGAL as a biomarker of acute kidney injury in patients undergoing percutaneous coronary interventions is presented.